Spectrum analysis of acoustic emission signal obtained during breakaway oxidation of 2.25Cr-1Mo steel - Jha B.B.; Mishra B.K.; Ojha S.N. (My University, 2025)
Frequency spectrum analysis of acoustic emission (AE) signal has been carried out during breakaway oxidation and internal cracking of oxide scales formed on 2.25Cr-1Mo steel. Three regions viz pre-breakaway, post-breakaway and internal cracking of scales have been distinguished based upon thermogravimetric analysis and SEM/EPMA observations. The frequency pattern of the AE signal obtained in three different regions shows three different characteristic features. Frequency spectra based upon the predominant frequencies have been correlated with the physical phenomena occurring during the course of oxidation. © (2009) Trans Tech Publications, Switzerland.